Catalytic, enantio- and diastereoselective synthesis of gamma-butyrolactones incorporating quaternary stereocentres - CONNON, STEPHEN (My University, 2012)
A new, highly enantio- and diastereoselective catalytic asymmetric formal cycloaddition of aryl succinic anhydrides and aldehydes which generates paraconic acid (y-butyrolactone) derivatives is reported.
PUBLISHED
Keywords: Chemistry